The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1517-83822011000400041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of Lippia alba essential oil: an alternative to control green molds

Abstract: The essential oil of Lippia alba is reported as an antifungal against human pathogenic microorganisms but few articles report its use as an alternative to synthetic fungicides on green mould control. The objective of this study was to determine chemical characteristics of L. alba essential oil and its antifungal activity against green molds as an alternative to synthetic fungicides. Essential oil was extracted by Clevenger hydrodistillation, characterized by GC-MS analysis, and the structure of the main compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 14 publications
3
31
0
4
Order By: Relevance
“…The antifungal activity against human pathogens was reported for genera such as Candida and Trichophyton for the citral and myrcene-citral chemotypes . Glamočlija et al (2011) reported antifungal activity against Aspergillus, Fusarium, Penicillium and Trichoderma genera. Although several studies analyzed the extracts of L. alba, specifically the essential oil, for microbiological control in plants (Rozwalka et al 2008), human health (Pessini et al 2003, Tempone et al 2008 and green molds (Glamočlija et al 2011), although the use of this plant or its extracts have not been reported for the control of basidiomycetes.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal activity against human pathogens was reported for genera such as Candida and Trichophyton for the citral and myrcene-citral chemotypes . Glamočlija et al (2011) reported antifungal activity against Aspergillus, Fusarium, Penicillium and Trichoderma genera. Although several studies analyzed the extracts of L. alba, specifically the essential oil, for microbiological control in plants (Rozwalka et al 2008), human health (Pessini et al 2003, Tempone et al 2008 and green molds (Glamočlija et al 2011), although the use of this plant or its extracts have not been reported for the control of basidiomycetes.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…Glamočlija et al (2011) reported antifungal activity against Aspergillus, Fusarium, Penicillium and Trichoderma genera. Although several studies analyzed the extracts of L. alba, specifically the essential oil, for microbiological control in plants (Rozwalka et al 2008), human health (Pessini et al 2003, Tempone et al 2008 and green molds (Glamočlija et al 2011), although the use of this plant or its extracts have not been reported for the control of basidiomycetes. Thus, the objective of this study was to evaluate the antifungal activity of L. alba on the mycelium of P. ostreatus for the control of wood white rottenness.…”
Section: Universidad Del Bío -Bíomentioning
confidence: 99%
“…Synthetic fungicides, for instance, are generally effective and inexpensive, but it has been suggested that they leave residual toxicity that may have carcinogenic and teratogenic side effects (McCarroll et al, 2002). Moreover, most of the synthetic fungicides have been restricted or banned in several countries since the early 1960s (Glamočlija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ex Britton & P. Wilson. Esta planta es un arbusto perteneciente a la familia Verbenaceae originaria de los Andes (Chile-Perú), y se le puede encontrar en las regiones tropicales y subtropicales de Centro, Suramérica y las islas del Caribe (Manica-Cattani et al 2009) y es ampliamente usada en las dos primeras zonas para diferentes propósitos (Glamočlija et al 2011). Su aceite esencial es producido principalmente en sus hojas a través del metabolismo secundario de la planta (Blank et al 2015).…”
Section: Introductionunclassified